The creative turn in evidence for public health: community and arts-based methodologies. (9th March 2018) - Byrne, E; Elliott, E; Saltus, R; Angharad, J
Abstract: Background: We propose that arts based methodologies can be of value in the production and exchange of evidence in supporting public health related policy. This article reports on a collaborative piece of work resulting from two projects which took place in a former coal mining town in South Wales. Methods: We used a participatory framework whereby researchers, community members and artists co-produced 'evidence' through the creative arts to inform public policy. We collected a range of data using a number of different techniques, including interviews, focus groups and observation, but also included an extensive range of creative activities. Results: The data provided a diverse range of perspectives on how people of different ages live their lives. The People's Platform was a performance-based debate which was the culmination of the collaboration. The show involved a series of short performances with time for facilitated discussion in-between. It was felt that the show facilitated knowledge exchange on health and wellbeing issues that are usually difficult to express and understand through traditional forms of evidence. Conclusion: Whilst arts-based approaches are not free from risk, they offer an alternative form of knowledge as a necessary complement to the range of data available to policy makers.